Novel doped hydroxyapatite thin films obtained by pulsed laser deposition - OKTAR, FAİK NÜZHET (ELSEVIER SCIENCE BV, 2013)
We report on the synthesis of novel ovine and bovine derived hydroxyapatite thin films on titanium substrates by pulsed laser deposition for a new generation of implants. The calcination treatment applied to produce the hydroxyapatite powders from ovine/bovine bones was intended to induce crystallization and to prohibit the transmission of diseases. The deposited films were characterized by scanning electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy, and energy dispersive X-ray spectroscopy. Pull-off adherence and profilometry measurements were also carried out. X-ray diffraction ascertained the polycrystalline hydroxyapatite nature of the powders and films. Fourier transform infrared spectroscopy evidenced the vibrational bands characteristic to a hydroxyapatite material slightly carbonated. The micrographs of the films showed a uniform distribution of spheroidal particulates with a mean diameter of similar to 2 mu m. Pull-off measurements demonstrated excellent bonding strength values between the hydroxyapatite films and the titanium substrates. Because of their physical-chemical properties and low cost fabrication from renewable resources, we think that these new coating materials could be considered as a prospective competitor to synthetic hydroxyapatite used for implantology applications. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Doped hydroxyapatite; Ovine/bovine bones; Highly adherent thin films; Pulsed laser deposition; MECHANICAL-PROPERTIES; COATINGS; GLASS; BHA; TEMPERATURE; COMPOSITES; OXIDE